Getting picky with the lysosome membrane. Issue 4 (3rd April 2021) - Lee, Chan; Overholtzer, Michael
ABSTRACT: Lysosomes play an essential role in quality control mechanisms by functioning as the primary digestive system in mammalian cells. However, the quality control mechanisms governing healthy lysosomes are not fully understood. Using a method to study lysosome membrane turnover, we discovered that LC3-lipidation on the lysosome limiting membrane is involved in invagination and formation of intralumenal vesicles, an activity known as microautophagy. This activity occurs in response to metabolic stress, in the form of glucose starvation, or osmotic stress induced by treatment with lysosomotropic compounds. Cells rendered deficient in the ability to lipidate LC3 through knockout of ATG5 show reduced ability to regulate lysosome size and degradative function in response to stress. These findings demonstrate that cells can adapt to changing metabolic conditions by turning over selective portions of the lysosomal membrane, using a mechanism that involves lysosome-targeted LC3 lipidation and the induction of selective microautophagy.